PEMILIHAN MATERI PEMBELAJARAN APRESIASI PUISI BERKARAKTER BANGSA DALAM NILAI RELIGIUS - Prayitno Prayitno (Jurnal Kependidikan)
Teachers in pre-learning activities of appreciation of poetry in high school need to select appropriate learning materials in order to meet the curriculum 2013. In 2013, the educational curriculum is oriented to national values, because it is one of the parts of the character education, which consists of education of values, education of ethics, education of moral, and education of characters. One of the implementations of the character education is by selecting instructional materials for appreciation of poetry that focuses on religious and nation values. In the pre-stage of this learning activity, the teacher needs to prepare the content of the poem that contains character education, namely religious and nation values, by means of interpreting connotative words, ambiguity associated with denotative words, and interpreting the meaning of the poem to understand its meaning. An alternative learning material of appreciation of poetry in high school can be taken from W.S. Rendra’s poems called Penance, After Confession, Come O God, Prayer of Hunger, and A Soldier's Prayer Before the War.